Institutional and organizational economics : a behavioral game theory introduction - Ellingsen, Tore (Medford : Polity Press, 2023)
"An analytical introduction to the dynamics of how societies succeed or fail"--
ESS
Hye Trade International
Keywords: Organizational sociology; Organization